Flaskô em luta: o estudo de uma fábrica sob controle operário no Brasil (2003-2019) - Romito, Gabriel Augusto (2019)
This research is the result of a study carried out during the year 2014 for the School of Sociology and Politics of São Paulo, whose aim was to approach the struggle against the capitalist mode of production. In this sense, the decision to choose Flaskô was based on the knowledge of its occupation from June 2003 to the present time. To that end, the questions that guide this dissertation and were at the heart of its problematization are the following: How can a factory be managed through the denial of a management system? And furthermore, how do the political subjects of this historical experience see themselves and build themselves as class in the face of the contradictions that the capitalist system impinges upon? Based on bibliographical discussions, semi-structured interviews and unstructured dialogues - after all, our source is the workers of the factory itself - this intellectual enterprise located in the theme of culture and work is intended to contribute to the historiographic production that concerns this segment as well as apprehend the general characteristics found in the plurality of forms of struggle of the working class. In addition, of course, to propose to contribute to the future organizational forms that deny the sociometabolism imposed by the current economic structure